Health Literacy in Iranian Women: A Systematic Review and Meta-Analysis - Elham CHAROGHCHIAN KHORASANI; Seyedeh Belin TAVAKOLY SANY; Arezoo OROOJI; Gordon FERNS; Nooshin PEYMAN (Tehran University of Medical Sciences, 2020)
Background: Inadequate health literacy (HL) is associated with poorer health outcomes and worse health care. Up to one-half of Iranian women have difficulty in interpreting medical information, and national HL assessment has been limited in Iran. We have undertaken a systematic review of the literature and used a meta-analysis to examine the situation of HL status in Iranian women, and determine the relationship between HL and self-efficacy, and self-care behaviors. Methods: Six databases (PubMed, Web of Science, Scopus, Google Scholar, Scientific Information Database) and other non-indexed citations were searched using a variety of keywords regarding HL and Iranian women. The bias risk was decreased by the involvement of two independent reviewers assessing study quality and eligibility of included articles. Results: The average HL scores were in the range of marginal or limited (63.08; 95% CI, 59.83-66.32) in the Iranian women. The HL score was significantly higher among pregnant women (67.55; 95% CI, 32.54- 82.57) and was lower in women with chronic disease (57.79; CI, 48.34-67.24). There was a significant association between HL and self-efficacy and self-care behaviors. Conclusion: The average level of HL in the period of the review was marginal among Iranian women. The relationship of HL with self-efficacy and self-care behaviors was statistically significant but moderate.